Adult autologous mesenchymal stem cells for the treatment of suspected non-infectious inflammatory diseases of the canine central nervous system: safety, feasibility and preliminary clinical findings. Issue 1 (December 2015) - Zeira, Offer; Asiag, Nimrod; Aralla, Marina; Ghezzi, Erica; Pettinari, Letizia; Martinelli, Laura; Zahirpour, Daniele; Dumas, Maria; Lupi, Davide; Scaccia, Simone; Konar, Martin; Cantile, Carlo
Abstract Background Non-infectious inflammatory diseases of the canine central nervous system (CNS) are common idiopathic disorders grouped under the term meningoencephalomyelitis of unknown origin (MUO). Ante mortem diagnosis is achieved via assessment of clinical signs, magnetic resonance imaging (MRI), and cerebrospinal fluid (CSF) analysis, but the definitive diagnosis needs histopathological examination. MUO are mostly considered as autoimmune CNS disorders, so that suppressing the immune reaction is the best management method for patients. Mesenchymal stem cells (MSCs) are under investigation to treat autoimmune and degenerative disorders due to their immunomodulatory and regenerative properties. This study aims to verify the safety, feasibility, and efficacy of MSCs treatment in canine idiopathic autoimmune inflammatory disorders of the CNS. Methods Eight dogs presented with acute onset and rapid progression of multifocal neurological signs were selected to the study. In all patients' physical and neurological examinations, MRI and CSF analyses were performed. Clinical diagnosis in all cases was MUO. All selected dogs responded initially to immunosuppressive drugs (prednisone and a combination of prednisolone and cytosine arabinoside) but developed undesirable side effects. For all eight dogs, the owners considered euthanasia but accepted cell therapy as a last possibility. Autologous bone marrow MSCs (BMMSCs), isolated, cultured, and expanded, were administered by intrathecal (IT) injection in the cisterna magna intravenously (IV) and by intra-arterial (IA) injection in the right carotid artery. Adverse effects and clinical response were monitored for 6 months up to 2-year follow-up. Results The use of autologous BMMSCs in dogs with MUO was safe for IT, IV, and IA injections. No major short- or long-term adverse effects were registered. All the dogs presented early improvement in their general and neurological conditions, with particular effect on cervical pain. The group of dogs treated by IT+IA administration showed a shorter time of reaction to therapy compared to the group treated by IT+IV administration. Conclusions MSCs treatment in dogs affected by MOU is safe and feasible. A larger group of dogs is needed to confirm these results as well as CNS histology in order to better understand the underlying mechanisms.